Hate Speech Through Identity Politics On Social Media Ahead Of The 2024 Presidential Election - Bajari, Atwar; Suryana, Asep; Wahyudin, Uud; Mulyana, Slamet; Rakhmaniar, Almadina (Jurnal Komunikasi, 2023)
The debate surrounding the 2024 General Election in the virtual space, such as social media, has led netizens to exchange hate speech and heavy criticism regarding their respective support. Two groups have emerged: government supporters highlighting the successes of President Joko Widodo and those shifting their support to Anies Baswedan after Prabowo joined the government. Over time, this phenomenon has led to the proliferation of hate speech based on identities such as religion, ethnicity, and fanatical groups, potentially dividing public opinion. This study aims to explain the emergence of hate speech and the forms of hate speech based on identity politics leading up to the 2024 General Election. This study employs virtual ethnographic analysis (Virtual Ethnography) to observe tweets or statuses on selected accounts and the comments that arise from those tweets. The objects of analysis are the trends of words and phrases and the content within observed sentences or paragraphs. The research findings have been presented in the form of tabulation and categorization. The results show that comments and statuses containing hate speech always create bidirectional and multi-directional communication models among users. Hate speech often uses phrases and keywords that lead to insults, malicious accusations, curses, and accusing the opposing party of being stupid and evil. Based on this study, social media users must realize that the presidential campaign is a time to have different choices but remain aware of the same nation. Users need to develop an awareness of social media ethics. Enforcing rules against those who spread hate speech is key for every actor involved.